RIRS with Vacuum-Assisted Ureteral Access Sheath versus MPCNL for the Treatment of 2-4 cm Renal Stone. (15th May 2020) - Lai, Dehui; He, Yongzhong; Li, Xun; Chen, Meiling; Zeng, Xingrong
Abstract : Objective . Comparison of outcomes between RIRS with vacuum-assisted ureteral access sheath (V-UAS) and MPCNL in the treatment of renal stone. Materials and Methods . 28 patients with 2-4 cm renal stone were treated using RIRS with 14/16 F V-UAS. The outcomes were compared to those who underwent MPCNL with 16 F Amplatz sheath using a matched-pair analysis in a 1 : 2 scenario. Matching criteria included stone size, location and laterality, gender, age, BMI, and degree of hydronephrosis. Patients' demographics, perioperative and postoperative characteristics, complications, stone-free rate (SFR), and auxiliary procedures were compared. Results . Mean operative times for the RIRS and MPCNL groups were 72.4 ± 21.3 minutes and 67.4 ± 25 minutes (P = 0.042 ). Postoperative pain was significantly less in the RIRS group. The initial SFR was 50% for the RIRS group and 73.2% for the MPCNL group (P = 0.035 ). The final SFR at postoperative three months improved to 89.3% for the RIRS group and 92.9% for the MPCNL group (P = 0.681 ). The auxiliary procedure rates were higher in the RIRS group (42.9% vs. 25%, P = 0.095 ). The overall complication rate in the RIRS group was lower, but the significant difference was not found. Conclusion . In the treatment of 2-4 cm renal stone, using V-UAS in RIRS can improve surgical efficiency with lower postoperative early pain scores. Comparing with MPCNL, its initial SFR was more depressed, and there is still a trend towards requiring more auxiliary procedures to achieve comparable final SFR.